ANALISIS FAKTOR PENDIDIKAN KEWIRAUSAHAAN, RELIGIOSITAS, MOTIVASI, DAN LINGKUNGAN SOSIAL YANG MEMPENGARUHI ENTREPRENEURIAL INTENTION - Faiza Muklis; Andri Novius; larbiel hadi (JURNAL AL-IQTISHAD, 2021)
The Objective of this study was to test the influence of entrepreneurial education variables, religiosity, motivation, and social environment on entrepreneurial intention of students of Islamic Universities in Riau Province. This research is a quantitative descriptive study by collecting data through distributing questionnaires, interviews, and observations.The results show that the variables of entrepreneurship education, religiosity, motivation, and social environment have a significant effect on entrepreneurial intention. Students' business intentions can be encouraged by providing an entrepreneurial curriculum that fosters student interest and creativity in entrepreneurship. The role of religiosity is also expected to increase business intention because Islamic universities have more religious curriculum content.